(untitled) - Gay, Grant (Boston, 2005)
The second edition of this market-leading text from the highly respected Gay and Simnett author team provides students with a solid theoretical grounding in auditing and assurance services. Now incorporating a strategic business risk approach, this second edition has a greater international focus and provides students with new practical examples of the theory in action. The authors' position at the forefront of industry development ensures that this text incorporates cutting-edge material consistent with leading discussion on the direction of the industry. This latest edition continues to lead the way with the inclusion of the most recent material on updated standards and practice
Keywords: Auditing,Textbooks,Kiểm toán; Australia,Úc